Green geopolymer cement with dry activator from geothermal sludge and sodium hydroxide. (15th April 2021) - Petrus, Himawan Tri Bayu Murti; Fairuz, Faaza Ihda; Sa'dan, Naala; Olvianas, Muhammad; Astuti, Widi; Jenie, S.N. Aisyiyah; Setiawan, Felix Arie; Anggara, Ferian; Ekaputri, Januarti Jaya; Bendiyasa, I Made
Abstract: Geopolymers have currently drawn great attention of scientists and engineers, mostly in the construction sector. The superior properties of geopolymer and waste valorization are the main factors of the application. To improve the workability and easiness application, a dry activator was implemented to produce a green and sustainable geopolymer. Dry activator was produced by calcining the mix of sodium hydroxide and either unwashed or washed geothermal sludge at a specified temperature. The dry activator was mixed with fly ash to produce the green geopolymer mortar. The compressive strength of the mortar was analyzed accordingly. Thus, the compressive strength as the response variable was processed with Research Surface Methodology (RSM) using minitab® 19. Meanwhile, the independent variables were the activator ratio (Na2 O/SiO2 ) and the calcination temperature 400, 500, and 650 °C. The optimum condition has been reached by using washed geothermal sludge calcined at 400 °C with a Na2 O/SiO2 ratio of 0.692 with 27.5 MPa of compressive strength. A more economical and sustainable green geopolymer is the concern of geopolymer applications nowadays. The green geopolymer produces less Carbon Dioxide compared to ordinary portland cement and geopolymer (concrete and mortar) as much as 31% and 23%. Highlights: Dry activator of geopolymer mortar. Geothermal sludge as sodium silicate substitute. One-ready mixed geopolymer with less carbon footprint. Geothermal power plant waste to valuable product.